Radiological and Clinical Presentation of Interstitial Lung Disease in Patients with Concomitant Psoriasis: A Cross-sectional Study - Manoj Meena; Aanchal Sharma; Shiv Prakash Sharma; Vinayak Mangal; Nandita Purohit (Journal of Clinical and Diagnostic Research)
Introduction: Psoriasis is a chronic inflammatory, immune-mediated proliferative skin disorder that predominantly involves skin, nails, and joints. Pulmonary manifestations, Interstitial Lung Disease (ILD), are very uncommon in psoriasis. Aim: To evaluate the radiological and clinical presentations of ILD in patients with concomitant psoriasis. Materials and Methods: This was a cross-sectional study that included 3,012 patients with psoriasis treated in the psoriasis clinic at the Department of Dermatology in SMS Medical College, Jaipur, Rajasthan, India, from March 2021 to February 2022 and 144 patients were referred to the Department of Respiratory Medicine with complaints of respiratory symptoms for comprehensive radiological, immunological, and clinical evaluation. Detailed history regarding ongoing drug therapy and demographic profile were collected, and radiographic characteristics were evaluated. Categorical data was expressed as a percentage (%), on the other hand, the continuous data were presented as the means±SD and median with 25th and 75th percentiles (interquartile range). Pearson’s correlation test was used to determine statistical differences between the study groups. Results: Out of the total patients, ILD was detected in 10 patients. The median age was 51.5 years (range 25-65), males and females were equally affected. The median time for the development of respiratory symptoms from the diagnosis of psoriasis was 24.5 months (range 6-60). Psoriasis Area and Severity Index (PASI) scores and time of development of respiratory symptoms from diagnosis of psoriasis were strongly and inversely correlated (r=-0.906) (p<0.001) with each other. Seven out of 10 patients (70%) had an High Resolution Computed Tomography (HRCT) pattern consistent with Usual Interstitial Pneumonia (UIP), 2 (20%) had fibrotic Non-Specific Interstitial Pneumonia (NSIP), and 1 (10%) had Combined Pulmonary Fibrosis and Emphysema (CPFE). Out of the 10 ILD patients, five patients were on immunosuppressive therapy, while five were not exposed to any immunosuppressive therapy. Conclusion: According to the findings in the present study, the immunological cascade in lung parenchyma in psoriasis patients having high PASI scores may lead to lung fibrosis.